Broadband light emitting zero-dimensional antimony and bismuth-based hybrid halides with diverse structures. Issue 44 (3rd November 2021) - Deng, Chenkai; Hao, Shiqiang; Liu, Kunjie; Molokeev, Maxim S.; Wolverton, Christopher; Fan, Liubing; Zhou, Guojun; Chen, Da; Zhao, Jing; Liu, Quanlin
Abstract : A series of hybrid metal halides were obtained, and among them, (TMEDA)3 Sb2 Br12 ·H2 O exhibits the strongest yellow emission centered at 625 nm with a full-width at half-maximum of ∼150 nm originating from self-trapped excitons. Abstract : Low-dimensional organic–inorganic metal halides have recently attracted extensive attention because of their various structures and distinguished photoelectric properties. Herein, we report a series of new zero-dimensional organic–inorganic hybrid metal halides: (TMEDA)3 Bi2 Cl12 ·H2 O, (TMEDA)3 Bi2 Br12 ·H2 O, (TMEDA)3 Sb2 Br12 ·H2 O, and (TMEDA)5 Sb6 Cl28 ·2H2 O [TMEDA = N, N, N ′·trimethylethylenediamine]. (TMEDA)3 M2 X12 ·H2 O (M = Bi or Sb, X = Cl or Br) crystallizes in the monoclinic space group P 21 / n, and (TMEDA)5 Sb6 Cl28 ·2H2 O crystallizes in the orthorhombic space group Pnma . (TMEDA)3 M2 X12 possesses a zero-dimensional structure with the metal halide ions of [MBr6 ] 3− isolated by the organic TMEDA 2+ cations. Interestingly, the (TMEDA)5 Sb6 Cl28 ·2H2 O structure consists of a combination of corner-connected octahedra [Sb4 Cl18 ] 6− and edge-shared [Sb2 Cl10 ] 4−, which is quite rare. The light emission of all these compounds was measured, and (TMEDA)3 Sb2 Br12 ·H2 O exhibits the most intense luminescence. Upon 400 nm ultraviolet light excitation, (TMEDA)3 Sb2 Br12 ·H2 O exhibited strong broadband yellow emission centered at 625 nm with a full-width at half-maximum of ∼150 nm originating from self-trapped excitons. This work suggests the possibility of new types of hybrid halides by introducing different metal centers and probing the structural evolution and photoluminescent properties, serving as a reference for the relationship between structure and luminescent performance and demonstrating their potential use as phosphors in light-emitting diodes.